The Palestinian-Israeli Conflict in the Memory of the Past the Jewish Nation: From Holocaust to Holocaust - Mubarok, Fahmi; Meidina, Ahmad Rezy (International Journal of Social Science and Religion (IJSSR), 2024)
This paper explores the dynamics of the Palestinian-Israeli conflict through the perspective of Jewish history and collective memory, with a particular focus on the Holocaust as a point of departure. Through a history of civilization approach and collective memory analysis, this paper explores how the traumatic experience of the Holocaust has shaped the identity, politics and narratives of the Jewish people to influence their views on the ongoing conflict in the Middle East. It reveals how the memory of the Holocaust is not only an integral part of Jewish identity but also plays a role in shaping the policies and strategies adopted by the state of Israel. Holocaust memory is often used to justify defensive and offensive actions to sustain the Jewish state amidst external and internal threats. In this context, the "From Holocaust to Holocaust" narrative reflects the transformation and continuity of collective trauma used as a legitimization and mobilization tool in the Palestinian-Israeli conflict. This paper uses historiographic methods and narrative analysis to identify recurring patterns of thought and feeling within the Jewish community and how these patterns translate into political action. It also highlights the role of critical actors, both political and intellectual, in shaping and articulating these narratives. The results of this paper are expected to provide deeper insights into the complexity of the Palestinian-Israeli conflict and how history and collective memory play an essential role in the dynamics of this conflict.